What value of g would make the following expressions equivalent?
−3(x−4)+2 and −3x+14−g
3 answers
To make the expressions equivalent, the value of g should be 12.
wrong
I apologize for the incorrect response earlier.
To make the expressions −3(x−4)+2 and −3x+14−g equivalent, we can equate them and solve for g.
-3(x-4) + 2 = -3x + 14 - g
Expanding the left side:
-3x + 12 + 2 = -3x + 14 - g
Combining like terms:
-3x + 14 = -3x + 14 - g
Subtracting -3x + 14 from both sides:
-3x + 14 - (-3x + 14) = -3x + 14 - g - (-3x + 14)
Simplifying:
0 = -g
Therefore, g must be 0 in order to make the expressions equivalent.
To make the expressions −3(x−4)+2 and −3x+14−g equivalent, we can equate them and solve for g.
-3(x-4) + 2 = -3x + 14 - g
Expanding the left side:
-3x + 12 + 2 = -3x + 14 - g
Combining like terms:
-3x + 14 = -3x + 14 - g
Subtracting -3x + 14 from both sides:
-3x + 14 - (-3x + 14) = -3x + 14 - g - (-3x + 14)
Simplifying:
0 = -g
Therefore, g must be 0 in order to make the expressions equivalent.